IJCM_263A: Vaccine Hesitancy in Tribal Communities: A Study on Parents of children under 5 years of age - Vishakan A S; Shaji Shibin M; Aswathy S (Wolters Kluwer Medknow Publications, 2024)
Background: People who delay or refuse vaccines for themselves or their children are presenting a growing challenge for countries seeking to close the immunization gap. Objective: To determine the proportion of vaccine hesitancy and associated factors among informants of children under five years of age (U-5) within tribal communities in Wayanad. Methodology: A cross sectional study was carried out in tribal colonies of Kalpetta taluk of Wayanad District. Sample size was calculated to 168 based on a study on vaccine hesitancy conducted among tribals at Murshidabad where the prevalence of vaccine hesitancy was 36.9% with an absolute error (d) = 7%. Out of the 175 colonies in the taluk of Kalpetta, 11 colonies were randomly selected. Informants of children ages < 5 years Vaccine hesitancy among parents and guardians was assessed individually for each child in the household. If the informants were hesitant to give any vaccine included in the national immunization schedule they were listed as vaccine hesitant. A total of 208 U-5 children informants were interviewed. Vaccine hesitancy was assessed by adopted SAGE questionnaire. Results: Mean age of the informants was 30.3 + 7.90 and of U-5 children were 2.87 years + 1.45. Majority of the informants were mothers of U-5 children (88.5%), more than 3/4th of the informants belonged to Paniya tribe, most of the participants were unemployed (64.9%). Vaccine hesitancy to any of the vaccine in the immunization schedule was found among 23 participants (11%), majority were hesitant to take Pentavalent vaccine 12(5.76%). Fear of needles, too many vaccinations at 1 sitting and adverse effects following vaccinations were common reasons for being hesitant. Conclusion: The vaccination program is driven by health workers reducing vaccine hesitancy, however with greater motivation and awareness among the community vaccine hesitancy can be further reduced.